Descriptions of larvae of four mainly DNA barcode-matched species of chlorocyphids from south-east Asia (Odonata: Chlorocyphidae) with notes on the generic and species level larval identification of Oriental region members of the family. - Orr, Albert G.w.; Dow, Rory A.; Steinhoff, Philip O.m. (Zootaxa, 2024)
The final stadium larvae of the following four species of south-east Asian Chlorocyphidae are described and compared: Aristocypha fenestrella (Rambur), Heliocypha biseriata (Selys), Libellago hyalina (Selys) and Sundacypha petiolata (Selys), including both sexes for the latter two species. Excepting one L. hyalina specimen from Brunei, identified by supposition based on habitat, all specimens were identified by comparing and matching the mitochondrial marker COI with that of known adult specimens from Sarawak, Brunei and several localities throughout tropical Asia. The specimens presented close matches with all adults in this gene. An assessment of the efficacy of this method of identification is provided, noting that in some cases close species cannot be separated by bar-code matching and ultimate determination is partially based on known distributions of adults. Some aspects of the relationships among genera revealed by the genetic analyses are also discussed. In addition, an exuvia of Libellago lineata (Burmeister) from northern Thailand, identified by supposition, is partially described for the purpose of comparison with L. hyalina. For the morphological analysis the unique features of chlorocyphid anatomy are discussed, and some new terminology is introduced. Overall, the morphological analysis revealed numerous clear differences between the four species studied, and comparisons with available literature suggest that some of these may be characteristic of their genera. It is also evident that in some cases clear interspecific differences occur within genera. It is however concluded that a generic level larval key for the Oriental region Chlorocyphidae based on morphology may never be attainable, although local generic or even species level keys addressing the fauna of limited geographic areas may be possible in many places, especially as the larvae of more species come to be known and described in detail.